1986
DOI: 10.1016/s0735-1097(86)80272-8
|View full text |Cite
|
Sign up to set email alerts
|

QT prolongation and the antiarrhythmic efficacy of amiodarone

Abstract: Amiodarone is an antiarrhythmic agent known to cause prolongation of action potential duration which is reflected in the electrocardiogram as a prolongation of the QT interval. Prolongation of the QT interval in patients dying suddenly was compared with that in patients who remained alive to determine whether a difference existed between these two groups. The electrocardiogram and amiodarone levels were evaluated in 33 patients who presented with cardiac arrest and symptomatic ventricular tachycardia in whom n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Its electrophysiologic effects as to other class 3 anti-arrhythmic drugs, through inhibition of potassium channels, are to prolong the action potential duration and effective refractory periods (Miller & Zipes, 2001) and hence prolongation of QT interval (Chabner & Knollman, 2011). Moreover, similar to class 4 anti-arrhythmic drugs, through inhibition of calcium channels, amiodarone can decrease the slope of pacemaker potential, reduction of HR and increase the PR interval (Torres et al, 1986;Winslow et al, 1990). Consistent with previous reports in our study amiodarone induced the PR and QTc interval prolongation that explains its anti-arrhythmic effect.…”
Section: Discussionsupporting
confidence: 92%
“…Its electrophysiologic effects as to other class 3 anti-arrhythmic drugs, through inhibition of potassium channels, are to prolong the action potential duration and effective refractory periods (Miller & Zipes, 2001) and hence prolongation of QT interval (Chabner & Knollman, 2011). Moreover, similar to class 4 anti-arrhythmic drugs, through inhibition of calcium channels, amiodarone can decrease the slope of pacemaker potential, reduction of HR and increase the PR interval (Torres et al, 1986;Winslow et al, 1990). Consistent with previous reports in our study amiodarone induced the PR and QTc interval prolongation that explains its anti-arrhythmic effect.…”
Section: Discussionsupporting
confidence: 92%
“…Since the gut wall contains CYP3A4, it is highly probable that these inhibitors act, at least in part, on the prehepatic amiodarone biotransformation [2–7]. These induced alterations of amiodarone metabolism could have clinical consequences: like amiodarone, N‐DEA has class III antiarrhythmic properties, but it also has some electrophysiological properties which differ from the parent drug, notably by a higher fast sodium channel blockade and lower class IV effects [38–43]. Experimental data have shown a correlation between N‐DEA plasma concentration and antiarrhythmic properties of amioda‐rone [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Several investigators have demonstrated only a weak or even an absent concentrationeffect relation. [16][17][18][19][20] Others found a clear concentration-related effect of amiodarone on QT-interval prolongation, slowing of heart rate, and suppression of ventricular arrhythmias. [21][22][23] The present study showed that for conversion of atrial fibrillation, plasma concentrations of desethylamiodarone were more important than those of the parent compound.…”
Section: Discussionmentioning
confidence: 99%